Położenie, powierzchnia i kształt wybranych jezior Pojezierza Międzychodzko-Sierakowskiego na mapach topograficznych - Kubiak, Jarosław; Ławniczak, Radzym (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2014)
The objective of research concerned verifying the accuracy of the location and shape of selected lakes presented on topographical maps from various periods, drawn up on different scales. The area of research covered lakes situated in North-Western Poland on the Międzychód-Sieraków Lakeland. An analysis was performed of vector maps available in both analogue and digital format. The shape and location of lakes have been verified directly by means of field measurements performed using the GPS technology with an accuracy class of RTK. A compilation of cartographic and field data formed the basis for a comparison of the actual area and the length of the shoreline of the studied lakes. Cartographic analyses made it possible to single out the most reliable cartographic sources, which could be used for the purposes of hydrographical analyses. The field measurements performed have also disclosed the potential for using differential GPS measurements for updating and verifying existing cartographic materials, including those pertaining to the hydrographic grid. Furthermore, they have made it possible to obtain very precise quantitative data.
Keywords: topographic maps; GPS; lakes geometry